Two grapevine metacaspase genes mediate ETI-like cell death in grapevine defence against infection of Plasmopara viticola. - Gong, Peijie; Riemann, Michael; Dong, Duan; Stoeffler, Nadja; Gross, Bernadette; Markel, Armin; Nick, Peter (Protoplasma, 2019)
Metacaspase, as hypersensitive response (HR) executors, has been identified in many plant species. Previously, the entire gene family of metacaspase has been uncovered, but there are still questions that remain unclear regarding HR-regulating gene members. In this study, based on metacaspase expression during different grapevine genotypes interacting with Plasmopara viticola, we identified MC2 and MC5 as candidates involved in HR. We overexpressed both metacaspases as GFP fusions in tobacco BY-2 cells to address subcellular localization and cellular functions. We found MC2 located at the ER, while MC5 was nucleocytoplasmic. In these overexpressor lines, cell death elicited by the bacterial protein harpin, is significantly enhanced, indicating MC2 and MC5 mediated defence-related programmed cell death (PCD). This effect was mitigated, when the membrane-located NADPH oxidase was inhibited by the specific inhibitor diphenylene iodonium, or when cells were complemented with methyl jasmonate, a crucial signal of basal immunity. Both findings are consistent with a role of MC2 and MC5 in cell death-related immunity. Using a dual-luciferase reporter system in grapevine cells we demonstrated both MC2 and MC5 promoter alleles from V. rupestris were more responsive to harpin than those from V. vinifera cv 'Müller-Thurgau', while they were not induced by MeJA as signal linked with basal immunity. These findings support a model, where MC2 and MC5 act specifically as executors of the HR.